Analisis SWOT Implementasi Penggunaan Aplikasi Livin by Mandiri - Febisatria, Andhi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to evaluate the implementation of the Livin’ by Mandiri application using the SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats). The application represents a digital transformation of Bank Mandiri’s banking services, designed to provide easy access and efficiency in financial transactions. Despite offering various advantages such as a wide range of features, a user-friendly interface, and the backing of Bank Mandiri’s trusted reputation, the application also faces several challenges, including technical issues, reliance on internet connectivity, and varying levels of digital literacy among users.The research uses a qualitative descriptive approach with a case study method, focusing on active users of the Livin’ application. Data were collected through interviews, direct observations, and documentation studies, with data validity ensured through triangulation.The analysis results show that the application has strong growth potential in line with the increasing public interest in digital banking services. To address the existing challenges, strategies are needed to improve security systems, develop innovative features, and collaborate with external parties such as fintech companies. Proper management of internal strengths and external opportunities, along with mitigation of weaknesses and threats, can help strengthen Livin’ by Mandiri’s position amid the growing competition in digital financial services.